The May Crosses ('Cruces de Mayo') of Piedrabuena, Spain: Ethnobotanical assessment of cultural and biological heritage with conservation implications for Erica and bryophyte species - Verde, Alonso; Francisco Zamora Soria; José Fajardo; Diego Rivera; Vicente Consuegra; Segundo ríos; Emilio Laguna; Concepción Obón; Arturo Valdés; Pablo Ferrer Gallego; Vanessa Martínez Francés; Francisco Alcaraz; et al. (Mediterranean Botany, 2026)
Religious festivities incorporating botanical elements constitute significant components of Spain's cultural heritage, exemplified by Corpus Christi, Palm Sunday, Béjar's "Moss Man," and Nativity scene representations. Among these biocultural manifestations, the "Cruces de Mayo" (May Crosses) festival represents a notable tradition wherein local communities establish altars featuring a cross adorned with elements from the surrounding natural environment. This ethnobotanical study focuses on the May Crosses tradition in communities along the Guadiana River valley, with particular emphasis on Piedrabuena (Ciudad Real province), where the festival demonstrates exceptional biocultural diversity.Through systematic field observations and semi-structured interviews with festival participants, we documented three distinct typological categories: Forest Crosses, Heather Crosses (predominantly featuring Erica species), and Mixed Crosses—the latter integrating both mineral elements (water and geological specimens) and botanical specimens. Our floristic inventory identified over 100 plant species utilized in these ephemeral botanical installations, with Heather Crosses representing particularly sophisticated botanical artworks deserving special cultural recognition.The research reveals significant conservation implications, as the tradition involves harvesting of some taxa with vulnerable conservation status. We present a preliminary assessment differentiating between abundant species suitable for sustainable wild collection and those requiring protection due to rarity, threatened status, or ecological sensitivity (including certain orchids, geophytes, and bryophytes). This study contributes to the understanding of biocultural heritage while addressing the urgent need for conservation-oriented management strategies that ensure the long-term sustainability of both the cultural practice and the botanical resources upon which it depends.
Keywords: Biocultural heritage; Cruces de Mayo; Ethnobotany; Erica species; Conservation biology; Traditional ecological knowledge; Ephemeral botanical art; Mediterranean flora; Plant harvest sustainability; Guadiana River basin; Religious ethnobiology; Cultural ecosystem services; Bryophyta; Mosses; Liverworts